Perbandingan Efisiensi Distribusi Produk Pertanian Melalui Rantai Pasok Tradisional dan Modern - Harahap, Lokot Muda; Batubara, Nur Aisyah; Manik, Rinalia Fauziah Br; Purba, Jui Fivri; Lingga, Rosi Dearan S (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research compares the distribution efficiency of agricultural products between traditional and modern supply chains. The method used is qualitative with secondary data analysis. Data were collected from company annual reports, official statistical data, journals and academic publications. The research results show that modern supply chains have several advantages over traditional supply chains, such as higher efficiency, better product quality, and more adequate infrastructure. Traditional supply chains have several weaknesses, such as dependence on farmers and traders, limited infrastructure, and limited technology. These weaknesses can lead to lower efficiency, lower product quality, and product loss.Modern supply chains can increase the efficiency of agricultural product distribution by using more modern technology, improving infrastructure, and implementing better management practices. The recommendations of this research are to encourage farmers and traders to switch to modern supply chains, and for the government to provide support and incentives for the development of modern supply chains.